Evaluation of condition on replacing repaired concrete based on NDT and the Mahalanobis–Taguchi system - Watanabe, Takeshi; Nouchi, Ayaka; Namerikawa, Susumu; Hashimoto, Chikanori (Frontiers in Built Environment, 2023)
In Japan, much infrastructure has been constructed over the past 50 years, and maintenance of such infrastructure is important. Repairing and retrofitting of deteriorated concrete members has become common place. Meanwhile, re-deterioration of repaired concrete members have become of concern. To prevent re-deterioration of repaired concrete members, it is important to evaluate quality and condition of repair, in addition to the use of NDE is required. Therefore, to evaluate condition of replacing repaired concrete specimens, ultrasonic test, Imapct-Echo test, and impact test for measuring mechanical impedance were applied. In addition, data of these NDT are integrated by Mahalanobis-Taguchi System (MT System). MT System is an information processing system for pattern recognition advocated by quality engineering. From the results, it is clarified that Mahalanobis distance calculated by the MT method could successfully evaluate the conditions of replacing repaired specimens.